Climate and density dependence cause changes in adult sex ratio in a large Arctic herbivore. Issue 2 (21st February 2017) - Peeters, Bart; Veiberg, Vebjørn; Pedersen, Åshild Ønvik; Stien, Audun; Irvine, Robert Justin; Aanes, Ronny; Sæther, Bernt‐Erik; Strand, Olav; Hansen, Brage Bremset
Abstract: Variation in adult sex ratio (ASR) affects population demography and dynamics of large mammals. The mechanisms behind this variation are largely unclear, but may be partly related to climatic drivers and density dependence operating differently on the adult male and female segments of the population. Here, we examine such drivers of annual changes in ASR in the predator‐free wild Svalbard reindeer ( Rangifer tarandus platyrhynchus ), a high Arctic subspecies whose population dynamics are shaped by climate. Using up to 35 year long time‐series of population count data from two populations, we disentangle drivers of fluctuations in ASR by first analyzing how climate and density dependence affect sex‐specific adult population growth rates through effects on mortality. There were a positive population size trend and an overall female bias in ASR throughout the study period. Increased winter precipitation, a proxy for the harshness of winter feeding conditions, was found to significantly reduce adult population growth rates through reduced survival in males, but not in females. However, increased population size tended to cause a stronger immediate decline in female than in male adult population growth rates. As a consequence, the female bias in ASR increased with harsher winter conditions and declined with higher population size. As expected from the increased frequency of rainy and icy winters due to climate warming, a recent trend toward increased female bias in ASR was evident. This demonstrates that climatic drivers of both short‐term fluctuations and long‐term trends in demography need to be accounted for in the management and population dynamic predictions of Arctic ungulates.